Muhammadiyah Senior Care : Innovations and Strategies For Social Services The Elderly In Yogyakarta - Muhammad Rifa'at Adiakarti Farid; Eka Anisa Sari (WELFARE : Jurnal Ilmu Kesejahteraan Sosial, 2021)
This study discusses Muhammadiyah Senior Care as an idea and innovation in social services. This model is part of the new characteristics in social service activities for the elderly. This in-depth study was carried out using a qualitative research approach with a descriptive type. Observations, interviews, and documentation that have been carried out are processed and analyzed by reducing data, displaying, and drawing conclusions. The results of this study indicate that Muhammadiyah Senior Care presents 3 steps of social services in the form of religious services, health services, and economic empowerment services. These three services are innovations as well as advocacy for the community to encourage increased social welfare.Keywords: Social Service, Elderly, Muhammadiyah, Empowerment, social advocacy